On-line preconcentration system for inductively coupled plasma atomic emission spectrometry with quinolin-8-ol and Amberlite XAD-2 resin - PORTA, Valerio; SARZANINI, Corrado; MENTASTI, Edoardo; ABOLLINO, Ornella (1992)
An on-line preconcentration system implemented with inductively coupled plasma atomic emission spectrometry (ICP-AES) was studied. For the retention of metal ions 8-hydroxyquinoline and Amberlite XAD-2 resin were used. This system improved the detection limits of Cd, Cu, Fe, Mn, Ni and Zn by a factor of 100 compared with ICP-AES alone. Owing to this sensitivity and the excellent selectivity towards the transition metal ions with respect to salt matrices, the method was successfully applied to the determination of the above metals in Antarctic sea water. The concentration found ranged between 16 ng l-1 (Mn) and 0.4-mu-g l-1 (Ni) with a precision of 10%.